2018
DOI: 10.1080/21691401.2018.1517769
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles toward bio and medical applications: review study

Abstract: Development of biologically inspired green synthesis of silver nanoparticles has attracted considerable worldwide attention in matter of medical science and disease treatment. Herein, the green synthesis of silver nanomaterials using organic green sources has been evaluated and discussed. These kinds of materials are widely used for treatment of antibiotic-resistant bacteria, cancer and etc due to their elegant properties compared with other chemical ways and drugs. Moreover, the outcome of green-based approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(104 citation statements)
references
References 100 publications
2
101
0
1
Order By: Relevance
“…Since long back, silver-based compounds have been used as antibacterial agent as they have strong antibacterial properties against various microorganisms [63][64][65][66][67][68][69][70][71][72]. Earlier studies have shown the antibacterial activity of biosynthesized NPs [73][74][75]29].…”
Section: Discussionmentioning
confidence: 99%
“…Since long back, silver-based compounds have been used as antibacterial agent as they have strong antibacterial properties against various microorganisms [63][64][65][66][67][68][69][70][71][72]. Earlier studies have shown the antibacterial activity of biosynthesized NPs [73][74][75]29].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to gold nanoparticles, silver nanoparticles also have anti-inflammatory, antibacterial, anti-cancer and other biological activities [ 290 ]. In recent years, researchers have been interested in the use of plant extracts, such as polyphenols, as reducing agents and stabilizers for green synthesis of silver nanoparticles [ 291 ].…”
Section: Nanoformulations For Loading and Delivery Of Polyphenolsmentioning
confidence: 99%
“…For instance, graphene has been credited for a variety of intriguing properties, such as exceptional thermal conductivity (5000 Wm À1 K À1 ), rapid electron mobility at ambient condition (250,000 cm 2 V À1 s À1 ), and excellent mechanical properties (Young's modulus up to 1 TPa) [3,[6][7][8]. Many attempts have been explored over different derivatives and composites of graphene, whereas synthesised Graphene Oxide (GO) without any further functionalisation process has been revealed as a toxic material.…”
Section: Introductionmentioning
confidence: 99%